Meningkatkan Kualitas Pelayanan Farmasi: Evaluasi Sistem Penyimpanan Obat Berdasarkan Standar Kefarmasian dan Prinsip Syariat Islam di Puskesmas Tlogosari Wetan Semarang - Kartika, Erza Ridha; Lola , Shofi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Pharmaceutical Services are direct pharmaceutical service activities to patients related to the provision of medicines with the aim of obtaining clear results in order to improve the quality of patients. Pharmaceutical service standards are a benchmark used as a guideline for pharmacists in implementing pharmaceutical services. Tlogosari Wetan Health Center, Semarang City is a parent health center that has 3 auxiliary health centers, including: Kekancan Mukti Health Center, Pedurungan Kidul Health Center, and Plamongansari Health Center. This study aims to evaluate the storage of pharmaceutical preparations Based on Pharmaceutical Service Standards at Tlogosari Wetan Health Center and Based on Islamic Sharia Principles. This study is descriptive using data collection techniques, namely interviews, observations, and documentation.